2005
DOI: 10.1017/s104795110500034x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting left ventricular remodelling and mechanics in the long-term follow-up after successful repair of aortic coarctation

Abstract: Patients who have undergone a seemingly successful surgical repair of aortic coarctation may have persistently abnormal geometry with a hyperdynamic state of the left ventricle. This is more frequent in older patients, and in those with higher diastolic blood pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
3
13
2
1
Order By: Relevance
“…However, it is worth noting that Corrected rabbits collectively had almost the same LV EF as CoA rabbits, with an LV mass similar to those in Control rabbits. These differences did not reach significance with the sample size of the current investigation, but may be hypothesis generating in terms of an acceptable BPG for the LV given other research from corrected CoA in a persistent hyperdynamic state(4, 5). …”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, it is worth noting that Corrected rabbits collectively had almost the same LV EF as CoA rabbits, with an LV mass similar to those in Control rabbits. These differences did not reach significance with the sample size of the current investigation, but may be hypothesis generating in terms of an acceptable BPG for the LV given other research from corrected CoA in a persistent hyperdynamic state(4, 5). …”
Section: Discussioncontrasting
confidence: 65%
“…Many of the long-term problems observed after treatments for CoA can be explained on the basis of abnormal cardiac and vascular biomechanics(3). For example, patients with primary or residual CoA may have a hyperdynamic and remodeled LV, if exposed to a prolonged increase in afterload(4, 5). …”
Section: Introductionmentioning
confidence: 99%
“…Este estudio demuestra que los pacientes con CoAo y HAS tuvieron un aumento del índice de masa ventricular izquierda, el cual tuvo una correlación inversa con la deformación longitudinal global; es decir, que a mayor índice de masa ventricular izquierda, menor deformación longitudinal. En cambio, la deformación radial estuvo aumentada, lo que podría estar relacionado con un estado hiperdinámico del VI, como se ha demostrado en pacientes con CoAo que han sido sometidos a una reparación quirúrgica aparentemente exitosa 22 , aunque otros autores, como Shimizu, et al 23 y Palmon, et al 24 , han demostrado que la hipertrofia crónica del VI se asocia con disfunción contráctil, por lo que la hipercontractilidad miocárdica que se encuentra en los pacientes con CoAo puede ser un arterfacto 25 . Gentles, et al 26 demostraron que el strain rate radial pico es una expresión de la contracción de la fibra de la pared media, y en presencia de poscarga baja tiene un comportamiento similar a la relación entre el estrés endocárdico y la velocidad, mostrando evidencia de un estado hipercontráctil inexplicable en los pacientes con CoAo, como nosotros hemos observado en nuestro estudio.…”
Section: Discussionunclassified
“…It has previously been shown that patients with repaired Coa are at risk of developing increased lV mass due to impairment of vascular mechanics, and abnormal blood pressure regulation 7,8 , especially in those with an angulated aortic arch, which in turn is associated with late hypertension 9 . However, little is known about how other factors interact with blood pressure and lV mass in this particular population.…”
Section: Introductionmentioning
confidence: 99%